The function is given as,
![f(x)=(1)/(5-6x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/bj062nor72hhkeybnppej2n5su7rrxvgup.png)
Differentiating both sides with respect to 'x',
![f^(\prime)(x)=(d)/(dx)((1)/(5-6x))](https://img.qammunity.org/2023/formulas/mathematics/high-school/lm7a8rtduv1yhgbloz6m5c1amf6739tywx.png)
According to the reciprocal rule,
![(d)/(dx)((1)/(g(x)))=(-g^(\prime)(x))/(g(x)^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/yn3rhtclz7ttsxhsukfwcwitqrn4wjok60.png)
Comparing with the expression,
![g(x)=5-6x](https://img.qammunity.org/2023/formulas/mathematics/high-school/ea6d9kh39icsvjumuw784xoosoewg2vn6o.png)
The corresponding derivative is given by,
![\begin{gathered} g^(\prime)(x)=(d)/(dx)(5-6x) \\ g^(\prime)(x)=(d)/(dx)(5)-6\cdot(d)/(dx)(x) \\ g^(\prime)(x)=0-6(1) \\ g^(\prime)(x)=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/zo8bg194tgo3pkdexi205bvvans1n9y6c5.png)
Substitute the values in the formula,
![\begin{gathered} (d)/(dx)((1)/(5-6x))=(-(-6))/((5-6x)^2) \\ (d)/(dx)((1)/(5-6x))=(6)/((5-6x)^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/hynxlcsfpbd3t99snz2ilw6n97df8plsw4.png)
So the derivative of the given function becomes,
![f^(\prime)(x)=(6)/((5-6x)^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/s6ehddr09rq5vposclvd8xdbbn67cgn1hg.png)
Thus, the derivative of the given function is obtained as,
![f^(\prime)(x)=(6)/((5-6x)^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/s6ehddr09rq5vposclvd8xdbbn67cgn1hg.png)